(untitled) (Web of Teachers: Inderscience Research, 2025)
In this article, the use of modern educational technologies in educational institutions is important in improving the effectiveness of the educational process. These technologies provide an interactivity and an individual approach, providing new opportunities for students to gain knowledge. Also, through modern educational technologies, the quality and results of education are improved, the performance of educators is increased, and the competitiveness of educational institutions is increased.